PROVENANCE STUDY ON SANDSTONE OF KATI FORMATION - Hamzah, Muhamad Hakimin (2016)
Kati Formation is composed of rocks of Upper Paleozoic age. It is located in mainly around of Kuala Kangsar and extends further south to Seri Iskandar. This research is to analyze and figure out the origin of the Kati Formation sandstones. Preliminary study on the three outcrops has been selected for the research. Sedimentary logs are created from all outcrop. There are mainly composed of interbedded sandstone, siltstone and mudstone. Petrographic analysis will be carried out to understand further about the rock in the area in terms of their mineralogy composition. The classification and provenance studies of the sandstones will be carried out on the basis of three important major detrital minerals like quartz, feldspar and lithic fragments. QFL triangular diagram will be used for the classification of the sandstones of Kati Formation. Kati Formation sandstones consist of fine to coarse poorly sorted feldspathic litharenite, litharenite and sublitharenite. Detrital framework grains included polycrystalline quartz, K- feldspar (microcline and plagioclase) and rock fragments. The origin of sediments were determined to be igneous and metamorphic terrains, probably of Sibumasu orogeny between IndoChina and East Malaya collision zones.